Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1108/ijoa-07-2018-1476
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of women managers’ resilience: conceptual discussion and implications for HRM

Abstract: Purpose This paper aims to provide a framework with the antecedents of women managers’ resilience in SMEs. Design/methodology/approach This developmental study uses a comprehensive literature review and a set of propositions to identify the antecedent of women managers’ resilience and develops a conceptual framework for resilience. Findings The results indicate that in addition to personal resilience traits, interactive engagement with the work environment, career adaptability and positive human resource m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 198 publications
(259 reference statements)
2
17
0
Order By: Relevance
“…Available evidence suggests that regardless of educational status, women are more likely to face workplace situations, which mould them to exhibit resilience [ 17 ]. Organisational factors such as reflective learning, coaching and career counselling and individual factors such as self-esteem, self-efficacy and career adaptability can improve resilience [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Available evidence suggests that regardless of educational status, women are more likely to face workplace situations, which mould them to exhibit resilience [ 17 ]. Organisational factors such as reflective learning, coaching and career counselling and individual factors such as self-esteem, self-efficacy and career adaptability can improve resilience [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…reflective learning, coaching and career counselling and individual factors such as self-esteem, self-efficacy and career adaptability can improve resilience [18].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The term resilience originates from the Latin verb "resilience" (to leap back), and it was first used in mathematics in the 1 7th century. The modern organizational sciences literature sees resilience from three different perspectives, n amely a trait or a capacity, or a process (Tabassum et al, 2019). Indeed, the concept of organizational resilience is seen as having such characteristics attributed to men (Witmer, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lekchiri, Crowder, Schnerre and Eversole (2019) conducted a study at a tertiary institution in Morocco and identified the following gender bias behaviours: abusive, verbal or physical or sexual harassment; unfair treatment; dismissal; and a lack of trust, recognition and acknowledgement. The most common constraints identified by various other studies include the glass ceiling, gender discrimination, organisational culture, work and family conflict, old boys network, stereotyping, poor support and personal characteristics (April & Sikatali, 2019;Cohen, Dalton, Holder-Webb, & McMillan, 2018;Khalid & Sekiguchi, 2019;Tabassum, Shafique, Konstantopoulou, & Arslan, 2019). According to Shepered (2017), women within the South African higher education context experience marginalisation, under-representation and the glass ceiling as the major obstacles in their career progression.…”
Section: Introductionmentioning
confidence: 99%